Baku - Valiyev, Anar (Elsevier, 2012)
Baku, the capital of the Azerbaijan Republic, was one of the major industrial cities in the Soviet Union. In contrast, the post-Soviet development of Baku has witnessed a major reconstruction with grandiose construction projects, which is meant to turn the city into a global city. Consequently, the urban landscape has been transformed in many parts of the city, while informal settlements and a deteriorating environment have become the main scourges of Baku. However, while the administration has attempted to follow the model of Dubai, in practice, the urban development is characteristically chaotic due to the absence of effective regulation and planning. Indeed, with the continued influx of oil revenue, the city is spending vast sums on new projects, buildings and infrastructure without any apparent strategic plan. This paper identifies the key forces and processes underlying the transformation of Baku and looks at the problems haunting the city.
Cities
Keywords: Baku (Azerbaijan) -- History.; Baku (Azerbaijan) -- Social conditions.; Architecture -- Azerbaijan -- Baku.; Urbanization -- Azerbaijan -- Baku.